Experimental investigation of operational E-PVC drying conditions on morphological properties of particles in a pilot-scale spray dryer. Issue 1 (2nd January 2023) - Mehrzad, Salem; Jamaati, Farzad; Dorfeshan, Masoud
Abstract: A Study of the process followed by an Emulsion Polyvinyl Chloride droplet in a spray dryer is necessary to understand the morphology of produced dry powder. For the Production of E-PVC, vinyl chloride monomer turns into liquid under pressure and high temperature. This liquid is extracted into the water in the form of emulsion with the help of an emulsifier, and polymerization is performed using water-soluble catalysts. Investigating the operational parameters of the latex drying process can provide helpful information for the design process. In the present study, a pilot plant of Arvand petrochemical spray dryer with a scale of 1:10 is constructed and studied. The purpose of this study is to experimentally analyze the drying of E-PVC in a pilot-scale spray dryer with a particular focus on determining the effects of drying conditions on the powder properties including morphology. For this purpose, the pilot-scale dryer is constructed, and the impact of various parameters such as inlet air temperature, atomization ratio, and latex concentration on outlet temperature and powder moisture content are investigated. A scanning electron microscope is employed to observe the particle morphology parameters mentioned above. The results showed that the outlet temperature decreased dramatically by increasing the atomization ratio and latex concentration. The results showed that more than 90% of the E-PVC particles are solid spheres. About 6% of donut-like particles, about 3% of particles with pore, less than 1% of broken hollow particles. The SEM image of latex used in experiments with a concentration of 40% and a Class D was taken to determine the shape of the latex particles. The picture showed that the particles were spherical before the drying, so the particles' final deformation is due to spray parameters changes during the drying process. From the morphological viewpoint, the number of agglomerates increased at higher inlet temperatures. More than 84% of particles maintained their spherical shape and have a diameter of 15-20 microns.